Russian regions and regionalism : strength through weakness - Herd, Graeme P.; Aldis, Anne, 1953- (RoutledgeCurzon, 2003)
This book examines the whole question of Russian regions and regionalism. It considers important themes related to regionalism, including demography, security, military themes and international relations.